Matrix isolation and spectroscopic properties of the methylsulfinyl radical CH3(O)S - Reisenauer, Hans Peter; Romanski, Jaroslaw; Mloston, Grzegorz; Schreiner, Peter R.; Justus Liebig University Giessen (My University, 2013)
The atmospherically highly relevantmethylsulfinyl radical CH3(O)S-center dot was generated thermally under flash pyrolysis conditions and isolated in Ar matrices at 10 K; the allyl radical is a byproduct. CH3(O)S-center dot and its D3- and C-13- isotopologues were characterized through the excellent agreement between experimental and computed IR and UV/Vis spectra.
Keywords: ddc:540